Understanding inequality and its evolution in Kenya: The contribution of the UNU-WIDER World Income Inequality Database initiative - Damiano Kulundu Manda; Germano M. Mwabu; Martine Oleche; Moses Kinyanjui Muriithi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Globally, there are several initiatives being undertaken to ensure the availability of information across countries that can be used to analyse the inequality phenomenon in and among countries. The data are easily accessible for use in comparative research on inequality across regions and countries, especially those covered by the UNU-WIDER World Income Inequality Database (WIID) initiative. This initiative is among the leading data innovations in the field of inequality research. This study explores how well the WIID Companion's standardized inequality measures relate to those derived using locally based data, such as the Kenyan inequality diagnostics and the fiscal incidence studies conducted by the African Centre of Excellence for Inequality Research (ACEIR). The findings show that the WIID Companion's standardized inequality measures are much higher than those in the original WIID, the Kenyan inequality diagnostic, and the fiscal incidence studies. The study demonstrates that inequality measures based on per capita consumption are likely to be lower than those based on net per capita income, partly due to the former not capturing the savings portion of disposable income. It is difficult to authenticate how well the WIID's standardized inequality measures relate to measures of per capita income inequality in Kenya due to lack of quality data on income and taxation. This issue needs to be investigated further as better data become available.
Keywords: C8; D3; E2; H3; I3; 330; inequality measures; data; WIID; Kenya